A set of biogenetically interesting polyhalogenated acetogenins from &ITPtilonia magellanica&IT - Gallardo Ovando, Amalia Beatriz; Cueto, Mercedes; Diaz-Marrero, Ana R.; de la Rosa, Jose M.; Fajardo Morales, Victor Manuel; San Martin Barrientos, Aurelio Del Carmen; Darias, Jose (My University, 2018)
Ptilonines A-F, pyranosylmagellanicus D-E and magellenediol are previously undescribed acetogenins isolated from the red alga Ptilonia magellanica. Their structures were determined from spectroscopic evidence. The absolute configuration of the known pyranosylmagellanicus A, was established by derivatization with (R)- and (S)-alpha-methoxy -alpha-phenylacetic acids (MPA). Ptilonines exhibit an unusual halogenation pattern, that may confer evolutionary advantages to Ptilonia magellanica, for which a biogenetic origin is proposed. The antimicrobial effect of some of these compounds was evaluated. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: ptilonia magellanica; bonnemaisoniaceae; red algae; ptilonines; pyranosylmagellanicus; magellenediol; unusual halogenation pattern; absolute configuration; biogenesis; strait of magellan